The Protection of Indigenous Peoples’ Seed Rights during Ethnobotanical Research - McCune, Letitia M. (Ethnobiology Letters, 2018)
Recognition of the importance of biodiversity for global food security and the community food sustainability movement has helped increase awareness of seed rights. International treaties created to ensure the world’s access to seed biodiversity address access to seed banks for breeding purposes. Ethnobotanists are often required to deposit research plant specimens with government seed banks or herbariums. If Indigenous Peoples’ plants are then used developing patented varieties, are their rights recognized? These rights depend upon recognition of Indigenous Peoples as plant breeders, prior informed consent (PIC) protocols, access and benefit sharing (ABS) agreements via material transfer agreements, and benefits returned to Indigenous and local communities per the Nagoya Protocol. To ensure such rights to genetic material and associated intellectual property rights, documentation of these agreements and links to the people and communities from which they originated needs to occur at first collection and throughout subsequent research, conservation, and breeding programs.